The Church: A Catalyst for Change in the Labor Movement - Mercado, Rosalinda C. (Philippine Journal of Labor and Industrial Relations; Vol 24 (2004): Philippine Journal of Labor and Industrial Relations, 2021)
This paper traces the involvement of the Church in the Philippine labor movement from the late 19th century up to the contemporary period. It defines the role of the church as a catalyst for social change as it struggles to maintain its relevance in a changing Philippine society characterized by the chronic turbulence and conflict. An attempt is made to analyze the role of the church particularly in its pursuit of social action which is a process that calls for actualization of Christian ethics and morality through positive and concrete action. A discussion is made on the various stages of the metamorphosis of the church vis-a-vis the social, political, and economic events during the period under study. The paper also shows the various shades of political and moral convictions of church elements.